Separate Evaluation of the Effects of Hydroalcoholic Extracts of Eryngium Caucasicum L. and Zataria Multiflora L. on Gastric Ulcers in an Animal Model - mahdi Jalahi; Mohammad Azadbakht; Jafar Akbari; Fereshteh Talebpuor; Fatemeh Akbari (Journal of Mazandaran University of Medical Sciences)
Background and purpose: The aging population and its associated complications, such as chronic pain, have led to an increased use of non-steroidal anti-inflammatory drugs (NSAIDs) like indomethacin. However, indomethacin is associated with notable side effects, particularly gastric ulcers. This study aims to investigate the potential protective effects of hydroalcoholic extracts of Zataria multiflora and Eryngium caucasicum in preventing indomethacin-induced gastric ulcers in an animal model. Materials and methods: In this experimental study, total phenol and flavonoid levels of the Zataria multiflora L. and Eryngium caucasicum L. plants were measured. Cultivated Artemia salina was used to evaluate the toxicity of the extracts. The animal study was conducted using eight groups of Balb/c mice. The groups included indomethacin at 70 mg/kg, omeprazole at 30 mg/kg, and three concentrations (250, 500, and 1000 mg/kg) of Eryngium caucasicum L. and Zataria multiflora L., respectively, administered individually to mice via gavage. One hour later, indomethacin was administered to the mice by gavage to induce gastric ulcers. Four hours after ulcer induction, the anesthetized animals were sacrificed, and their stomachs were removed for histopathological and morphological evaluation. Results: The amount of total phenol in Zataria multiflora L. and Eryngium caucasicum L. plants was 113.5 mg/ml and 26.06 mg/ml, respectively, and the flavonoid content of these plants was 41 mg/ml and 16.79 µg/ml, respectively. The toxicity results of cultivated Artemia salina showed that the toxicity of Zataria multiflora and Eryngium caucasicum plants was 500±0.0012 ppm and 0.0031±0 ppm, respectively. The histopathological results showed that Zataria multiflora and Eryngium caucasicum played an effective role in reducing inflammation, bleeding in stomach tissue, and congestion. Furthermore, the results showed that a dose of 1000 mg/kg was more effective than lower doses for both extracts. Conclusion: Hydroalcoholic extracts of Eryngium caucasicum  and  Zataria multiflora plants demonstrated a protective effect against stomach ulcers. This effect appears to be attributed to the presence of phenols and flavonoids in the extracts and is dose-dependent.